THEORETICAL BASIS OF LABORATORY COURSE IN PHYSICS UBAYDULLAEV SADULLA (International Conference on Economics, Finance, Banking and Management, 2025)
In the process of studying physics, laboratory exercises arouse natural interest in students, they are associated with knowing the world around them through their own experience and feelings. When performing laboratory work, students develop an understanding of the role of experiments in life. Experimental skills, which include mental and practical skills, are formed in students through experiments. The purpose of laboratory exercises is, first of all, to independently search for information, methods and techniques for completing assigned tasks, to assess their quality, to develop training, education and personal competencies that allow students to apply the knowledge gained in practical activities. When planning laboratory work, it should be taken into account that, along with the leading didactic goal, students also develop practical skills and qualifications in working with laboratory equipment, as well as research skills. The analysis of these issues is the main content of our article.